PENGEMBANGAN BAHAN AJAR BERBASIS KEARIFAN LOKAL UNTUK PEMBELAJARAN IPA DAN IPS DI KELAS IV SDN 17 PONTIANAK KOTA - Santoso, Ichsan; Kresnadi, Hery; Ghasya, Dyoty Auliya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to develop teaching materials based on local wisdom for natural and social science learning, specifically Chapter 6, "Indonesiaku Kaya Budaya", for Grade IV students at SDN 17 Pontianak Kota. The research employs a development (R&D) approach using the ADDIE model. Quantitative data were obtained from validation results and practicality questionnaires filled out by teachers and students, while qualitative data were derived from validator suggestions, teacher notes, and student feedback. Data collection techniques included interviews and questionnaires. The findings revealed that the teaching materials are valid and practical, as evidenced by the following results: content expert validation achieved an average score of 4.25, categorized as "valid"; design expert validation achieved an average score of 4.11, categorized as "valid"; and language expert validation achieved an average score of 4.25, also categorized as "valid." Furthermore, the practicality evaluation by teachers achieved an average score of 4.64, categorized as "very practical." The practicality evaluation by a small group of students resulted in an average score of 3.81, categorized as "practical," while the large group evaluation achieved an average score of 4.47, categorized as "very practical." Based on these findings, it can be concluded that the teaching materials based on local wisdom are feasible and practical to support learning activities.